INTELLEGENCE INFLUENCE OF MOTIVATION AND LEARNING PHYSICS STUDENTS THROUGH APPLICATION OF CONCEPT MAPPING STRATEGY - I Putu Brama A.D.; Undang Rosidin; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
This study aimed to determine: (1) Is there any influence between the intelligence of students' physics student learning outcomes through the implementation of the concept mapping strategy? (2) Is there any influence of motivation to learn physics student learning outcomes through the implementation of the concept mapping strategy? The research was carried out directly in class X 6 semester at SMA N 5 Metro, totaling 230 students. Effect between intelligence and motivation towards physics student learning outcomes can be measured by conducting tests in the form of test blocks and test practice. Learning outcomes data that have been obtained are then tested using a normality test, homogeneity, and anova test two paths. Based on the research that has been done, it can be concluded that: (1) There is influence between the intelligence of students with physics student learning outcomes through the implementation of the concept mapping strategy. (2) There is the influence of the motivation to learn the physics student learning outcomes through the implementation of the concept mapping strategy.Keywords: intelligence, motivation, learning outcomes.